Arylation of N‐Methyl‐2‐oxindole with Arylboronic Acids in Water Catalyzed by Palladium(II) Pincer Complexes with a Low Catalyst Loading. Issue 6 (20th February 2017) - Vignesh, Arumugam; Kaminsky, Werner; Dharmaraj, Nallasamy
Abstract: Two new Pd II ONO pincer complexes were utilized efficiently as homogeneous catalysts for the site‐selective C3‐arylation of N ‐methyl‐2‐oxindole with arylboronic acids at room temperature in aqueous media to yield a series of 3‐aryl‐ N ‐methyl‐2‐oxindoles. This catalytic reaction progressed well with a low catalyst loading (0.01 mol %) under open‐flask conditions. Notably, a column‐chromatography‐free method for the quantitative preparation of C3‐arylated N ‐methyl‐2‐oxindoles is reported. The catalyst showed good compatibility with wide range of substrates with recyclability in up to five consecutive runs without an appreciable loss of yield. Abstract : Power of palladium pincer complex : Two new Pd II ONO pincer complexes are utilized efficiently as homogeneous catalysts for the site‐selective C3‐arylation of N ‐methyl‐2‐oxindole with arylboronic acids at room temperature in aqueous media to yield a series of 3‐aryl‐ N ‐methyl‐2‐oxindoles.